Computational fluid dynamics simulation of fluidized bed dryer for sago pith waste drying process - Abdul Mu’im Abdul Nasir,; Masli Irwan Rosli,; Mohd Sobri Takriff,; Nur Tantiyani Ali Othman,; Vinotharan Ravichandar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sago pith waste (SPW) has a great potential in becoming numerous kinds of reusable products as it has high level of starch content after went through drying process. Without proper treatment the disposal of SPW could cause serious environmental problem. The drying process of SPW using fluidized bed dryer (FBD) was found to be more effective than other drying methods. Thus, in this study the process was analyzed using computational fluid dynamics (CFD) modelling with the developed three-dimensional FBD model. The fluidization profile was studied from the analysis done using ANSYS Fluent 19.2 software which include certain process flow and set up to create similar situation as the experimental condition by also taking into account the moisture content of SPW. Both approach of drying process were executed at air inlet temperature of 50ºC and velocity at 1.50 ms-1. Using the sample of SPW that initially at 40% wet basis the result of fluidization from experimental and simulation were comparable in term of particles profiles and percentage of moisture content which show closely resemblance of decreasing trend. The outcome was however having a slight different of moisture content at 15th minute of experimental approach which could be resolved by improving the model in term of zone condition of the simulation setup. This study is however is an initial part to study about SPW drying using CFD solution as there are more to be discovered with this advantageous tool that is able to perform and provide much more analysis and outcomes in much shorter time and cost saving way base on the experimental method.